Development and validation of an algorithm to accurately identify atopic eczema patients in primary care electronic health records from the UK - Abuabara, K.; Magyari, A.M.; Hoffstad, O.; Jabbar-Lopez, Z.K.; Smeeth, L.; Williams, H.C.; Gelfand, J.M.; Margolis, D.J.; Langan, S.M. (Elsevier, 2017)
Electronic health records hold great promise for clinical and epidemiologic research. Undertaking atopic eczema (AE) research using such data is challenging due to its episodic and heterogeneous nature. We sought to develop and validate a diagnostic algorithm that identifies AE cases based on codes used for electronic records used in the UK Health Improvement Network (THIN). We found that at least one of 5 diagnosis codes plus two treatment codes for any skin-directed therapy were likely to accurately identify patients with AE. To validate this algorithm, a questionnaire was sent to the physicians of 200 randomly selected children and adults. The primary outcome, the positive predictive value (PPV) for a physician-confirmed diagnosis of AE, was 86% (95%CI 80-91%). Additional criteria increased the PPV up to 95% but would miss up to 89% of individuals with physician-confirmed AE. The first and last entered diagnosis codes for individuals showed good agreement with the physician-confirmed age at onset and last disease activity; the mean difference was 0.8 years (95% CI -0.3,1.9) and -1.3 years respectively (95%CI -2.5, -0.1). A combination of diagnostic and prescription codes can be used to reliably estimate the diagnosis and duration of AE from the THIN primary care electronic health records in the UK.